Analisa Pengaruh Customer Experience Terhadap Customer Satisfaction Wisatawan Pada Destinasi Wisata Kabupaten Bintan Kepulauan Riau - Iranita Iranita (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2018)
This study discusses the customer experience that supposedly affects customer satisfaction of tourists in the province of Riau Islands of Bintan Regency. In this study the variable dimension measured through experinece sense, feel, think, act and relate. Research data processed with using their analysis of multiple linear regression and factor. The results of this research show that customer experience significant influential variable and positive towards consumer satisfaction (customer satisfaction). The result of the research shows that experience variable with dimensions of sense, feel, think, act and relate simultaneously against influential customer satisfaction. In partial dimensions factor sense, feel, think and relate that give may influence against the satisfaction and sense of dominant influence dimensions against customer satisfaction.